Soil compaction limits for Ilex paraguariensis (Research, Society and Development, 2020)
The objective of this work was to verify the effect of different soil compaction degree on the development of Ilex paraguariensis. The study was conducted in a greenhouse at UNICENTRO in Guarapuava, PR. For the culture implantation, pots of 0.15 m diameter were made with PVC tubes, subdivided into rings. The upper and lower ring presented thickness of 0.20 m and were subjected to soil compaction degree (GC) of 75%, while the intermediate ring presented thickness of 0.05 m, and received GC of 75, 80, 85, 90 and 95%. It was verified a negative effect of the mate herb growth due to soil compaction, being the soil compaction degree of 85% more favorable for the development of the Ilex paraguariensis.